1991
DOI: 10.1039/c39910001281
|View full text |Cite
|
Sign up to set email alerts
|

A low temperature reaction sequence for methane conversion

Abstract: Surface carbonaceous intermediates produced from methane are shown to produce small alkanes upon hydrogenation below 400 K.Current practice to convert natural gas to higher hydrocarbons proceeds by the indirect route in which natural gas is first converted to synthesis gas at a high temperature.1 Subsequently, hydrocarbons are produced in a low temperature exothermic process from synthesis gas.2.3 Direct methane conversion, like pyrolysis to acetylene and benzene, can only operate at temperatures above 1200 K.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(44 citation statements)
references
References 7 publications
1
42
0
1
Order By: Relevance
“…It can be seen that promotion of the Ru catalyst with vanadium increased the fraction of carbon which was adsorbed in the reactive C a form. The selectivities for products produced from this C,, fraction are also found to be affected by vanadium promotion: the n-hexane selectivity is seen to pass through a maximum with 0.33 wt.% V. In agreement with previous studies [13], we have All product selectivities were measured during hydrogenation at 110°C.…”
Section: Effect Of Vanadium Promotion On Labelled N-hexane Selectivitysupporting
confidence: 78%
See 1 more Smart Citation
“…It can be seen that promotion of the Ru catalyst with vanadium increased the fraction of carbon which was adsorbed in the reactive C a form. The selectivities for products produced from this C,, fraction are also found to be affected by vanadium promotion: the n-hexane selectivity is seen to pass through a maximum with 0.33 wt.% V. In agreement with previous studies [13], we have All product selectivities were measured during hydrogenation at 110°C.…”
Section: Effect Of Vanadium Promotion On Labelled N-hexane Selectivitysupporting
confidence: 78%
“…During the high temperature adsorption it is generally accepted that three types of surface carbon species are formed, and these are generally referred to as Ca, Ct3 and Cv [11][12][13]. TPR studies of the ~C surface species has shown evidence for the existence of both C,~ and C, with maxima in ~ l CH 4 production at 110°C and 200°C, respectively.…”
Section: High Temperature 11c 1 Formationmentioning
confidence: 99%
“…In heterogeneous catalysis, various metals have been discovered that can chemisorb CH 4 at moderate temperatures and that can decompose CH 4 to C and H 2 at higher temperatures. Amariglio and co-workers [5] and van Santen and co-workers [6] independently and almost simultaneously reported a "two-step" process.…”
Section: Direct Conversion Of Ch 4 Under Nonoxidative Conditions: a Bmentioning
confidence: 99%
“…Ichikawa and coworkers found that the formation rates of C 6 3 crystallites, and some of them migrate into the zeolite channels and interact with the Brønsted acid sites. Depending on the zeolite used and the preparation methods, the optimum Mo loading for MDA ranges from 2 to 6%.…”
Section: The Bifunctionality Of the Mo/hzsm-5 Catalystsmentioning
confidence: 99%
“…Figure 7 compares the amount of products formed during hydrogenation, after separate methane and propene adsorption and their co-adsorption. Surface carbon from methane alone can be hydrogenated to Cz+ hydrocarbons [48]. However, most of the dissociatively adsorbed methane reacts back towards methane.…”
Section: Resultsmentioning
confidence: 99%